Van buitenwereld tot buitenstaander - Pierrart, Thomas (Internationale Neerlandistiek, 2020)
Abstract Despite his growing popularity, the Dutch writer Auke Hulst (1975), whose oeuvre ranges from multimedia travel books to science fiction-like novels, has remained under-researched in academic scholarship. This paper provides an introduction to this author and an analysis of his work, examining Hulst’s self-presentation, his poetics, his (non-)fictional books and his place within contemporary Dutch literature. The image of the outsider, which is of vital importance for Hulst’s authorship, runs as a continuous thread throughout the discussion. The first section uses several assertions made in interviews, public talks and forewords to elaborate on Hulst’s ‘autobiographical’ poetics and to elucidate how the author often presents himself as a ‘literary’ outsider (positioning himself outside the constraints of Dutch literature) and as a ‘social’ outcast (in relation to his traumatic childhood). The second section deals with Hulst’s travel books, in which he conjures up the image of a solitary traveler, who flees from the burdens of home and society in search for freedom, authenticity, insight and connectedness. The third section discusses Hulst’s novels, which are centered on outcasts, the (inner and outer) worlds they find refuge in, and the obstacles they are confronted with. In the final section, Hulst’s outsider position in Dutch literature is critically revisited by connecting his oeuvre with twenty-first-century literary trends.
Keywords: self-presentation